Ethnic Differences in Attending a Tertiary Dementia Clinic in Israel - Specktor, Polina; Ben Hayun, Rachel; Yarovinsky, Natalia; Fisher, Tali; Aharon Peretz, Judith (Frontiers in Neurology, 2021)
Introduction: Variations in lifestyle, socioeconomic status and general health likely account for differences in dementia disparities across racial groups. Our aim was to evaluate the characteristics of Arab (AS) and Jewish (JS) subjects attending a tertiary dementia clinic in Israel. Methods: Retrospective data regarding subjects attending the Cognitive Neurology Institute at Rambam Health Care Campus between April 1, 2010, and April 31, 2016, for complaints of cognitive decline were collected from the institutional registry. AS and consecutive JS, aged ≥50 years without a previous history of structural brain disease, were included. Results: The records of 6175 visits were found; 3246 subjects were ≥50 years at the initial visit. One hundred and ninety-nine AS and consecutive JS cases were reviewed. Mean age at first visit was 68.4±8.8 for AS and 74.3 for JS (p<0.0001). Mean education was 7.7±4.8 years for AS and 11.3 years for JS (p<0.0001). Mean duration of cognitive complaints prior to first visit did not differ between the groups. Initial complaints of both ethnicities were failing memory (97%) and behavioral changes (59%). Functional impairment was reported by 59% of AS and 45% of JS (p=0.005). MMSE on first evaluation was 19.2±7 for AS and 23.1±5.9 for JS; p=0.001. Alzheimer’s disease was diagnosed in 32% AS and 23% JS, mild cognitive impairment in 12% AS and 21% JS. Normal cognition was diagnosed in 2% AS and 9% JS; p=0.0001. Conclusions: Compared to JS, AS attend a tertiary clinic when their cognitive impairment already affects their functional abilities providing a comprehensive benchmark for social health care interventions to reduce disparities.